Non-immune hydrops fetalis secondary to congenital chylothorax with diffuse interstitial lung disease: a diagnostic conundrum - Ngeow, Alvin Jia Hao (BMJ Case Rep, 2021)
A Chinese male infant was born at 35 weeks weighing 2935 g to a mother with polyhydramnios and prenatal hydrops fetalis. He developed marked respiratory distress secondary to bilateral congenital chylothorax and required pleural drainage, high frequency oscillation and inhaled nitric oxide therapy. He was extubated to non-invasive ventilation by day 14. There was no bacterial or intrauterine infection, haematologic, chromosomal or cardiac disorder. He was exclusively fed medium-chain triglyceride formula. High-resolution CT showed diffuse interstitial lung disease. He received a dexamethasone course for chronic lung disease to facilitate supplemental oxygen weaning. A multidisciplinary team comprising neonatology, pulmonology, haematology, interventional radiology and thoracic surgery considered congenital pulmonary lymphangiectasia as the most likely diagnosis and advised open lung biopsy, lymphangiography or scintigraphy for diagnostic confirmation should symptoms of chylothorax recur. Fortunately, he was weaned off oxygen at 5 months of life, and tolerated human milk challenge at 6 months of life and grew well.